Language in cognition - Seuren, Pieter A. M. (Oxford : Oxford University Press, 2009)
In this text, Pieter Seuren presents a different perspective on the study of linguistic meaning, the place of logic in language and the embedding of language in cognition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psycholinguistics; Semantics (Philosophy); Connotation (Linguistics)